Alternative Spring Break at the Savannah College of Art and Design: Engaging Art and Design Students in Community Service. Issue 162 (December 2014) - Hoey, J. Joseph; Feld‐Gore, Jeffrey A.
Abstract : This chapter describes the impact of an alternative spring break program on students at the Savannah College of Art and Design over a set of years as well as its effectiveness as a service‐learning tool.